Occurrence of Hemerobius stigma Stephens in pine bast scale (Matsucoccus spp.) populations: opportunistic predation or obligatory association? (Bollettino di zoologia agraria e bachicoltura, 2024)
Hemerobius stigma Stephens (Neuroptera: Hemerobiidae) occurs naturally in coniferous forests of western and central Europe. Based on field and laboratory observations conducted mainly by European researchers, H. stigma has been accurately defined as predator of aphids (Hemiptera: Aphidoidea), often observed on spruce and fir trees. Hemerobius species were among several insect predators collected from epidemic populations of Matsucoccus (Hemiptera: Matsucoccidae). Collection of H. stigma from pine trees infested with M. pini Green in the 1970s and M. feytaudi Ducasse in the early 1990s suggests for the first time a close relationship between H. stigma, Matsucuccus, and pine. However, there was no data confirming that these Hemerobius spp. feed and successfully develop on Matsucoccus. The first evidence of interrelationship between H. stigma and Matsucoccus was obtained using pheromone traps in field studies conducted in maritime pine (Pinus pinaster Ait.) stands in central Portugal which show that H. stigma is highly attracted to sex pheromone of maritime pine bast scale M. feytaudi. It was also lured by the pheromone of M. matsumurae Kuwana, originating in the pine forest of the southern Asia, but not by the sex pheromone of M. josephi Bodenh., occuring in the East Mediterranean.The frequent occurrence of H. stigma in aphid colonies, documented as suitable feed for the brown lacewing on the one hand and the strong specific kairomonal response of the lacewing to certain sex pheromone of Matsucoccus on the other, raise the question about the essence of the lacewing and the scale predator-prey relationship. To address this question, we tested the capability of H. stigma to prey and develop on Matsucoccus, using M. josephi and Cinara palaestinensi Hille Ris Lambers (Hemiptera: Lachnidae) as prey models. Further, we activated traps baited with the sex pheromone of M. feytaudi to compare the seasonal population trends of males of M. feytaudi with those of adult H. stigma and Elatophilus crassicornis Reuter (Heteroptera: Anthocoridae). The latter is a specific predator of M. feytaudi in Portugal, also attracted to the sex pheromone of both M. feytaudi and M. matsumurae. In the laboratory, both M. josephi and C. palaestinensis have served as appropriate food for H. stigma, allowing its complete development for successive generations and verifying its wide range of prey species among hemipteran taxa. However, the seasonal flight  pattern of H. stigma, as obtained by trap captures was not correlated with that of the M. feytaudi males, whereas a significant correlation was observed between the seasonal flight of E. crassicornis and that of males of M. feytaudi. A possible explanation to the interrelationship between Hemerobius stigma - Matsucoccus feytaudi - pine is presented and discussed.
Keywords: scale insects; sex pheromone; kairomonal response; plurithropic interactions